1978
DOI: 10.1016/0584-8539(78)80167-6
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra in the CH stretching region and the structure of the polymethylene chain

Abstract: C-H stretching regions of both the Raman and i.r. spectra of the extended polymethylene chain have broad secondary maxima. In the case of the Raman spectrum, line shapes are dependent on the environment of the chain, a fact which has been previously exploited in the study of biosystems. We have explained this phenomenon in terms of Fermi resonance interaction between the methylene symmetric C-H stretching mode and appropriate binary combinations involving the methylene bending mode. It is emphasized that appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
682
0
10

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 794 publications
(719 citation statements)
references
References 29 publications
27
682
0
10
Order By: Relevance
“…This has also been confirmed for lipid droplets monitored by CARS microspectroscopy (31). In addition, a slight frequency shift of the symmetric CH 2 peak can be noted, also characteristic of lipids in liquid phase (29). Thus, our data strongly suggest that the shift in metabolism to increased lipid storage observed for the stressed daf-2 and -4 (dauer) mutants is accompanied by a shift in the ordering of the lipids from gel (high ordering) to liquid (low ordering) phase.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…This has also been confirmed for lipid droplets monitored by CARS microspectroscopy (31). In addition, a slight frequency shift of the symmetric CH 2 peak can be noted, also characteristic of lipids in liquid phase (29). Thus, our data strongly suggest that the shift in metabolism to increased lipid storage observed for the stressed daf-2 and -4 (dauer) mutants is accompanied by a shift in the ordering of the lipids from gel (high ordering) to liquid (low ordering) phase.…”
supporting
confidence: 50%
“…In contrast, it is found to be insignificant relative to the symmetric CH 2 vibration (Ϸ2,845 cm Ϫ1 ) for these two species. In Raman spectroscopy, the ratio between the asymmetric and symmetric CH 2 vibrations is used to determine the ordering of polymethylene chains (29) and phospholipids (30). A higher ratio is obtained for the gel phase, characterized by highly ordered methyl chains, compared with the liquid phase with less-ordered chains.…”
mentioning
confidence: 99%
“…Saturated fatty acids have an ordered arrangement at room temperature and this results in a strong peaks for both the symmetric and antisymmetric CH2 stretches. The ratio of these peak heights is dependent on the crystallinity of the sample in crystaline samples the anti-symmetric peak is more intense than the symmetric peak [30]. Unsaturated fatty acids are liquid at room temperature, in their spectra the 2840cm -1 peak is still present but the peak at 2870cm -1 is less pronounced and incorporated in a much broader peak between arround 2860-2930cm -1 [31,32].…”
Section: C) Srs A) B) Carsmentioning
confidence: 99%
“…Looking for an internal standard for measuring its intensity changes in going from one diamine to another, and its temperature variation for the same diamine, we have used its integrated area calculated from a lorentzian fit related to the integrated area of the entire N-H (3110-3360 cm À1 ) and N-D (2250-2550 cm À1 ) stretching regions, respectively. Like the observed for the integrated areas of the C-H stretching regions of n-alkanes [4], also the integrated areas of those stretching regions were found to remain constants to within a few percent, either for the different studied diamines, or for the same diamine, at different temperatures.…”
Section: The Intensity Changes Of the C-c Stretching Mode And The Avementioning
confidence: 61%
“…Moreover, in order to study the environment interactions-both lateral packing and top-to-end-special attention should be paid to the changes observed in the C-H stretching region. In fact, for hydrocarbon chains it has been observed that while the band due to the methylene C-H antisymmetric mode broadens, loses intensity and shifts to higher frequencies, as the intermolecular lateral interactions decrease, the symmetric stretching one remains sharp as well as the most intense feature in the spectrum [2,4]. A quantitative measure of this lateral order was thus developed [2], as a function of the relative observed intensity of the C-H symmetric and antisymmetric stretching bands.…”
Section: Introductionmentioning
confidence: 99%